Circulating Sestrin Levels Are Increased in Hypertension Patients. (13th June 2020) - Fang, Cao; Yang, Zicong; Shi, Lei; Zeng, Tao; Shi, Ying; Liu, Ling; Liu, Hongtao; Lin, Yingzhong
Abstract : Background . Sestrins (Sesns), a group of oxidative stress-related proteins, have been reported to be involved in various cardiovascular diseases, including aortic dissection and chronic heart failure. This study is aimed at investigating the level of circulating Sesn1, Sesn2, and Sesn3 in hypertension patients. Methods . Plasma levels of Sesn1, Sesn2, and Sesn3 in 400 hypertensive patients and 100 normotensive subjects were detected using enzyme-linked immunosorbent assay (ELISA) kits. The hypertension patients were divided into groups with grade I (n = 140 ), grade II (n = 180 ), and grade III (n = 80 ) hypertension. Results . Compared with the normotensive subjects, Sesn1, Sesn2, and Sesn3 levels were increased in patients with hypertension, with a gradual increase between the groups with grade I, grade II, and grade III hypertension. Elevated Sesn1, Sesn2, and Sesn3 levels were positively correlated with both the systolic blood pressure (SBP) and diastolic blood pressure (DBP). Moreover, Sesn1, Sesn2, and Sesn3 levels were elevated in patients with dipper hypertension and further increased in patients with nondipper hypertension. In addition, smokers, as well as patients with higher levels of angiotensin II (Ang II) and carotid atherosclerotic plaque (CAP), exhibited increased Sesn1, Sesn2, and Sesn3 levels when compared with patients without these clinical characteristics. Furthermore, plasma levels of Sesn1, Sesn2, and Sesn3 were negatively correlated with the presence of CAP. Conclusions . Circulating Sesn levels are increased in patients with hypertension and may be a target for the prevention and treatment of clinical hypertension.